Sibling species composition and feeding pattern of malaria vectors in indoor-sprayed and non-sprayed districts of Lira and Kole, northern Uganda - Rashid Mwesige; John Paul Byagamy; Robert Opiro; Harriet Angwech; David Onanyang; Patrick Buchan Ocen; Stephen Ochaya; Geoffrey Maxwell Malinga (Malaria Journal)
Abstract Background Vector control interventions using long-lasting insecticidal nets and indoor residual spraying are common tools deployed for the control of malaria in Uganda. To evaluate the effectiveness of these control tools and understand the prevailing malaria vectors, a study was conducted to determine the species composition, indoor resting population density and biting pattern of malaria vectors in indoor residual spraying (IRS) and non-indoor residual spraying (non-IRS) districts of Lira and Kole, Northern Uganda. Methods Both indoor and outdoor adult malaria vectors were sampled using Human-Baited Catch and Pyrethrum Spray Catch methods from August to September 2022. Mosquitoes collected were identified to species level using morphological keys and species-specific polymerase chain reaction (PCR) assays. The indoor and outdoor time of biting of the mosquitoes were also recorded. Results The indoor residual densities (IRD) of anopheles populations in non-IRS sprayed district of Kole did not differ significantly from residual sprayed district of Lira (Man-Whitney U-test, U = 7.0, P = 0.400, N = 6). However, Anopheles gambiae sensu stricto (s.s.) dominated the vector population (43.1%, 44/102) in the non-IRS district, followed by An. funestus (30.4%, 31/102) and Anopheles arabiensis (26.5%, 27/102). In the IRS district, Anopheles funestus was the predominant species (52.3%, 23/44), followed by An. gambiae s.s. (34.1%, 15/44) and An. arabiensis (13.61%, 6/44). In IRS district, An. funestus and An. gambiae s.s. had an indoor biting peak of 03:00–04:00 h and outdoors from 21:00–1:00 h. Conclusion The findings have important implications for malaria control interventions in areas where IRS is actively used for vector control. However, more longitudinal, ecological, and genetic studies are needed to better understand the entomological impact of indoor residual spraying in northern Uganda.